RESULT ANALYSIS OF FRICTION STIR WELDING OF ALUMINUM 5083 H112 USING TRIANGULAR PIN TOOL WITH VARIATION IN ROTATIONAL AND TRANSLATION SPEED - Yazid, Muhammad
Needs of aluminium as material for the manufacture of transportation vehicle is very large in Indonesia. Joint process such as welding is needed for producing large-sized transportation vehicle. Friction stir welding is a type of welding without melting the workpiece. The welding is done by the presence of friction between the tool and the workpiece. This research was conducted to determine the effect of rotation and translation speed on the quality of welding result in 10 mm-Aluminium 5083 H112. The tool used is AISI H13 Steel with a threaded triangular pin shape. This pin has a triangle length of 9 mm and a pin length of 9.5 mm. The type of thread used is the right thread. The results of optimization process produce parameter variatons on translation speed and dwell treatment. The varied translation speeds were 50 mm/min and 75 mm/min at a rotation speed 1500 rpm. The weld areas such as weld nugget (WN), heat affected zone (HAZ), and thermomechanically affected zone (TMAZ) have been changed in microstructure caused by the process of welding. Differences in parameters will cause in the size of formed defect. The value of joint strength, hardness, and toughness have increased with an increase in translation speed. The best welding result are produced by welding parameter with translation speed 75 mm/min.